ANALISIS PENGARUH PERTUMBUHAN ASET,UKURAN PERUSAHAAN, PROFITABILITASDAN RISIKO BISNIS TERHADAP STRUKTUR MODAL SUB SEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA - Naur, Birgita Maryeta; Nafi', Moch (University of Merdeka Malang, 2017)
The purpose of this study was to examine the effect of asset growth, firm size, profitability and business risk simultaneously on the capital structure.The population of this study there are companies manufacturing sub-sectorsof food and beverages listed on the Stock Exchange during 2010-2015. The total number of samples is 5 companies. The sampling technique used was purposive sampling. The method of data analysis that uses regression and statistical description. The size of the company, Profitability and the business risk is partially not significantly affect the capital structure. Asset growth has a significant effect on the capital structure partially. Simultaneously variable firm size, profitability, asset growth and business risk significant influence terhasap capital structure. The results showed of four independent variables, firm size, profitability and business risk significantly affect the capital structure is simply asset growth. The three others variable despite having influence, but not significant. Raise capital to take advantage of outside capital into opportunities that can be used see the low risk businesses owned most of the companies manufacturing sub-sectors of cosmetics and household use.Â DOI: https://doi.org/10.26905/ap.v3i1.1327